2014
DOI: 10.1002/dys.1475
|View full text |Cite
|
Sign up to set email alerts
|

A Perceptual Learning Deficit in Chinese Developmental Dyslexia as Revealed by Visual Texture Discrimination Training

Abstract: Learning to read involves discriminating between different written forms and establishing connections with phonology and semantics. This process may be partially built upon visual perceptual learning, during which the ability to process the attributes of visual stimuli progressively improves with practice. The present study investigated to what extent Chinese children with developmental dyslexia have deficits in perceptual learning by using a texture discrimination task, in which participants were asked to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…(2) The Character Recognition Measure and Assessment Scale for Primary School Children (CRM: Wang & Tao, 1993). CRM is a standardized written vocabulary test, which has been commonly used to examine participants' reading skill in Chinese studies (Yeung, Ho, Chan, & Chung, 2014;Wang et al, 2014;Meng et al, 2011;Yang & Bi, 2011;Yang et al, 2013;Qian & Bi, 2014). In this test, characters are divided into 10 groups based on reading difficulty (174 characters for the fourth graders and 210 characters for the fifth graders), which corresponds with the standard difficulty coefficient.…”
Section: Participantsmentioning
confidence: 99%
“…(2) The Character Recognition Measure and Assessment Scale for Primary School Children (CRM: Wang & Tao, 1993). CRM is a standardized written vocabulary test, which has been commonly used to examine participants' reading skill in Chinese studies (Yeung, Ho, Chan, & Chung, 2014;Wang et al, 2014;Meng et al, 2011;Yang & Bi, 2011;Yang et al, 2013;Qian & Bi, 2014). In this test, characters are divided into 10 groups based on reading difficulty (174 characters for the fourth graders and 210 characters for the fifth graders), which corresponds with the standard difficulty coefficient.…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies have indicated that the visual perceptual processing (e.g., the low-spatial-frequency sensitivity, geometric-figure processing) had an impact on the recognition and encoding processes during Chinese reading in typically developed children and adults (Luo et al, 2013; Yang et al, 2013; Zhao et al, 2013, 2014). Various studies have shown that Chinese individuals with developmental dyslexia exhibit visual deficits (Chung et al, 2008; Wang et al, 2010; Meng et al, 2011; Qian and Bi, 2014), and visual function training for dyslexics can improve their reading-related skills (Meng et al, 2014; Wang et al, 2014; Qian and Bi, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, visual attention span has been found to relate to visuospatial and global processing when participants had to process multiple units (Xue et al, 2013). Given that global visual processing plays an important role in Chinese reading (Wang et al, 2014), it is necessary to explore the relationship between the visual rapid simultaneous processing and reading fluency in Chinese.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies of pre‐school children from different cultures indicate that early at‐risk factors of dyslexia should include tests of VS (see i.e. Wang et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%